Features of emotional burnout in psychologists working in the field of mental health during war - Maruta Наталія; Panko Тамара; Fedchenko Вікторія; Semikina Олена; Yavdak Ірина; Kosovskyi Володимир; Honcharenko Ігор (Psychosomatic Medicine and General Practice, 2026)
Relevance. Assessing the state of emotional burnout among mental health professionals during the war is extremely relevant. Aim. To assess emotional burnout among psychologists working in municipal psychiatric care facilities during the war. The materials and methods. Included the “Questionnaire of sociodemographic indicators of medical workers in the field of mental during the war”, the methodology of K. Maslach and S. Jackson (Maslach Burnout Inventory - MBI), the methodology of the “Professional Quality of Life Assessment Scale” (PROQOL-5), the questionnaire for measuring burnout (BAT) (work-related version) - part 1 and part 2, the questionnaire “Coping Strategies” by R. Lazarus, mathematical processing methods. The survey was conducted among 39 clinical psychologists and psychologists during the war, working in municipal psychiatric care. Results. It was established that 100.00% of psychologists have a syndrome of emotional burnout of varying degrees of severity. The assessment of working conditions during the war was characterized by the compounding effects of an increase in the number of patients, heightened tension, worsening psychological conditions, and reduced financial support for the organization of the work process. The assessment of the professional quality of life of psychologists showed an average level of indicators on the scales "Satisfaction with compassion" and "Burnout" and a low level of indicators on the scale "Compassion fatigue / Secondary traumatic stress" in the majority of those surveyed. The ambiguous role of coping strategies in the formation of emotional burnout was determined: maladaptive coping strategies (confrontational and escape-avoidant coping) contribute to increased emotional exhaustion. Adaptive coping strategies do not affect the increase in emotional burnout in psychologists. A particularly important role is identified between all coping strategies and the reduction of personal achievements, which is supported by strong positive relationships between these indicators. Keywords: emotional burnout, psychologists, war УДК 616.89:159.944:159.9-051:355.01